Command Speech Acts on Health Services: A Sociopragmatics Study - Pujiati, Tri (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
This research was conducted as an effort to see the form of directive speech on command speech acts based on a gender perspective carried out by students at the College of Health Sciences when providing health services. This research using a sociopragmatic approach was carried out at the College of Health Sciences in South Tangerang. This research with a qualitative descriptive design is expected to be able to provide an overview of students' use of directive speech acts of command speech acts based on a gender perspective. This research used an instrument by filling in a Discourse Completion Test (DCT) which was given to 60 students with a proportional distribution, 30 men and 30 women. The results of the research show that there are different forms of directive speech in commanding speech for male and female speakers when providing services to the general public who come from different social classes, educational backgrounds, health insurance, and gender. The differences in the use of directive speech of command speech acts when providing health services are done as an effort to establish communication with interlocutors who come from different backgrounds. The results of this research conclude that students have good abilities in speaking directive speech when communicating with interlocutors who have different social variables.